MASK: A Game-Based Learning Model for Developing Fundamental Movement Skills in Elementary Physical Education - Masleha Rasihati; Aprizal Fikri; Noviria Sukmawati; Muslimin; Dewi Septaliza (STKIP Pasundan, 2026)
This study aimed to develop the MASK learning model (Mengajar Ala Spinner dan Kartu) as an innovative instructional medium for improving fundamental movement skills among Phase C elementary school students. Employing a Research and Development approach with the ADDIE model, the study involved expert validation, small-scale field testing, and large-scale field testing across several public elementary schools in Gumay Ulu District, Lahat Regency. Data were collected through expert judgment, observation, and performance-based assessments. The results indicated that the MASK learning model met acceptable validity criteria and demonstrated practical feasibility in classroom implementation. Findings from both small- and large-scale trials showed that most students achieved good to very good performance levels in locomotor, non-locomotor, and manipulative skills, accompanied by increased engagement and motivation during learning activities. These results suggest that the MASK learning model constitutes a valid and effective instructional alternative for elementary Physical Education learning grounded in physical literacy principles.